Pioneering BRCA1/2 Point-Of-Care Testing for Integration of Germline and Tumor Genetics in Breast Cancer Risk Management: A Vision for the Future of Translational Pharmacogenomics - Mampunye, Lwando; van der Merwe, Nerina C.; Grant, Kathleen A.; Peeters, Armand V.; Torrorey-Sawe, Rispah; French, David J.; Moremi, Kelebogile E.; Kidd, Martin; van Eeden, Petrus C.; Pienaar, Fredrieka M.; Kotze, Maritha J. (Frontiers in Oncology, 2021)
Research performed in South African (SA) breast, ovarian and prostate cancer patients resulted in the development of a rapid BRCA point-of-care (POC) assay designed as a time- and cost-effective alternative to laboratory-based technologies currently used for first-tier germline DNA testing. In this study the performance of the new assay was evaluated for use on a portable screening device (ParaDNA), with the long-term goal to enable rollout at POC as an inventive step to meet the World Health Organization's sustainable development goals for Africa. DNA samples for germline testing were obtained retrospectively from 50 patients with early-stage hormone receptor-positive breast cancer referred for genomic tumor profiling (MammaPrint). Currently, SA patients with the luminal-type breast cancer are not routinely selected for BRCA1/2 testing as is the case for triple-negative disease. An initial evaluation involved the use of multiple control samples representing each of the pathogenic founder/recurrent variants included in the BRCA 1.0 POC Research Assay. Comparison with a validated laboratory-based first-tier real-time polymerase chain reaction (PCR) assay demonstrated 100% concordance. Clinical utility was evident in five patients with the founder BRCA2 c.7934delG variant, identified at the 10% (5/50) threshold considered cost-effective for BRCA1/2 testing. BRCA2 c.7934delG carrier status was associated with a significantly younger age (p=0.03) at diagnosis of breast cancer compared to non-carriers. In three of the BRCA2 c.7934delG carriers a high-risk MammaPrint 70-gene profile was noted, indicating a significantly increased risk for both secondary cancers and breast cancer recurrence. Initiating germline DNA testing at the POC for clinical interpretation early in the treatment planning process, will increase access to the most common pathogenic BRCA1/2 variants identified in SA and reduce loss to follow-up for timely gene-targeted risk reduction intervention. The ease of using cheek swabs/saliva in future for result generation within approximately one hour assay time, coupled with low cost and a high BRCA1/2 founder variant detection rate, will improve access to genomic medicine in Africa. Application of translational pharmacogenomics across ethnic groups, irrespective of age, family history, tumor subtype or recurrence risk profile, is imperative to sustainably implement preventative healthcare and improve clinical outcome in resource-constrained clinical settings.